2008
DOI: 10.1177/1077559507307837
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between Adolescent Reports of Childhood Abuse and Child Protective Service Determinations in an At-Risk Sample of Young Adolescents

Abstract: This study examines the concordance between adolescent reports of abuse and abuse determinations from Child Protective Service (CPS) agencies. It also compares the utility of adolescent reports of abuse, relative to CPS determinations in predicting adolescent psychological adjustment. The sample included 350 early adolescents, ages 12 to 13 years, who were initially identified prior to age 2 years as being at elevated risk of maltreatment. An Audio-Computer Assisted Self Interview (A-CASI) was used to assess l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
180
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(194 citation statements)
references
References 45 publications
11
180
3
Order By: Relevance
“…This method of inquiry has been shown to be highly reliable among general child welfare populations (Everson et al 2008). Also, in light of the overwhelming majority of empirical evidence highlighting pathological symptoms instead of discovering competencies of these youth, an examination that aims to identify their strengths alongside their trauma histories and sequels is warranted.…”
mentioning
confidence: 99%
“…This method of inquiry has been shown to be highly reliable among general child welfare populations (Everson et al 2008). Also, in light of the overwhelming majority of empirical evidence highlighting pathological symptoms instead of discovering competencies of these youth, an examination that aims to identify their strengths alongside their trauma histories and sequels is warranted.…”
mentioning
confidence: 99%
“…To test whether the effect of abuse is mediated by psychological distress, we again followed the 4 steps identifi ed by Baron and Kenny. 40 Abuse predicts abdominal pain and nausea/vomiting (step 1, Table 3). Psychological (β = 0.20, t = 5.5; P <.001), physical (β = 0.12, t = 3.5; P <.001), and sexual abuse (β = 0.15, t = 4.4; P <.001) predicted anxiety/ depression (step 2).…”
Section: Retrospective Self-report Of Abuse and Gastrointestinal Sympmentioning
confidence: 99%
“…[37][38][39] In addition, at age 12 years, self-report of lifetime (birth to 12 years) abuse was assessed through an Audio-Computer Assisted Self-Interview with 3 instruments developed for the LONGSCAN project. 40 The Self Report of Physical Abuse and Assault assessed physical abuse, ranging from being kicked or punched to such offenses as being stabbed or shot by an adult. The Self Report of Sexual Abuse and Assault assessed increasingly severe sexual experiences, including nocontact experiences (eg, someone making you look at something sexual, such as a picture), fondling, oral-genital contact, and penetration.…”
Section: G a S T Roin T Es T Ina L Sy Mp To Ms A Nd Chil D M A Lt R Ementioning
confidence: 99%
“…The authors concluded that there is little evidence of distinction between substantiation status and unsubstantiation, and that unsubstantiated reports should not be dismissed as they do not represent the absence of maltreatment. Other studies also recognize that defining child maltreatment in terms of legal criteria and CPS investigation data is inadequate for assessing the scope and magnitude of the problem and significantly underestimates the incidence and prevalence of child maltreatment (Coohey, 2007;Cross & Casanueva, 2009;Crume et al, 2002;Everson et al, 2008;Hussey et al, 2005;Kohl et al, 2009;Runyan et al, 2005;Sedlak et al, 2010;and Swahn et al, 2006;Theodore et al, 2005). It is possible that the use of substantiation for screening, investigation, or service provision may leave many actual and potential maltreatment victims unrecognized and consequently unprotected and underserved.…”
Section: Maltreatment Substantiationmentioning
confidence: 99%
“…is inadequate for assessing the scope and magnitude of the problem and significantly underestimates the incidence and prevalence of child maltreatment (Coohey, 2007;Cross & Casanueva, 2009;Crume et al, 2002;Everson et al, 2008;Hussey et al, 2005;Kohl et al, 2009;Runyan et al, 2005;Sedlak et al, 2010;and Swahn et al, 2006;Theodore et al, 2005). Though the DR model of CPS practice provides the opportunity to recognize and assist children and families in need without official determination or substantiation of maltreatment and without reporting the alleged perpetrator to a central registry, it is possible that the DR model of CPS practice contributes to underestimation of child maltreatment incidence and prevalence, underreporting of suspected maltreatment, and failure to identify repeat perpetrators.…”
Section: Limitationsmentioning
confidence: 99%